Enhancing Clinical Relevance of GLIM Criteria in Acute Pancreatitis: A Call for Integrated Practice [Letter] - Zhu ML; Liu XY (International Journal of General Medicine)
Mei-lin Zhu,1 Xiang-yu Liu2 1Department of Geriatrics, Jining No. 1 People’s Hospital, Jining, Shandong Province, 272000, People’s Republic of China; 2Department of Gastroenterology, Jining No. 1 People’s Hospital, Jining, Shandong Province, 272000, People’s Republic of ChinaCorrespondence: Xiang-yu Liu, Jining No. 1 People’s Hospital, No. 6 Jiankang Road, Jining, Shandong Province, 272000, People’s Republic of China, Tel +86 18678758605, Email lxyu8765@163.com